2022
DOI: 10.1155/2022/2368564
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Bisphosphonate on Osteocyte Proliferation and Bone Formation in Patients with Diabetic Osteoporosis

Abstract: Background. Bisphosphonate is currently considered one of the drugs for the first-line treatment of osteoporosis because of its ability to inhibit bone resorption, but the molecular mechanism of its effect on osteocyte proliferation and bone formation of diabetic osteoporosis is still unclear. Objective. To confirm the potential effect on of bisphosphonate on osteocyte proliferation and bone formation in patients having diabetic osteoporosis (DO). Methods. Sixty DO patients admitted to our hospital from Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The general information of the included studies is shown in Table 1 . The 22 studies [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ] had a total of 11,852 participants. The sample size of the studies ranged from 23 to 7718.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general information of the included studies is shown in Table 1 . The 22 studies [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ] had a total of 11,852 participants. The sample size of the studies ranged from 23 to 7718.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [ [21] , [22] , [23] , [24] , 28 , 32 , 34 , 38 ] reported data on P1NP. Since there was statistical heterogeneity among them ( I 2 = 93.1 %, P = 0), a random effects model was used.…”
Section: Resultsmentioning
confidence: 99%
“…The role of TBS as an everyday tool that is meant to follow-up the effects of antiosteoporotic drugs, as seen for DXA-BMD/T-score, is still controversial, but numerous studies addressed this issue; whether TBS is more useful in T2DM patients than BMD is yet to be proven. On the other hand, so far, no ideal drug against diabetes-induced osteoporosis has been found, and typically the management of the diabetic osteoporotic patients is similar to the non-diabetic individuals in addition to a good glycemic control [6,[76][77][78].…”
Section: Interventional Approach For Osteoporosis In T2dm Patientsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%